Audit Delays Before and During the Pandemic: Are Financial Distress and Profitability Important? - Nella Juwita Tarekar; Aisyaturrahmi Aisyaturrahmi (Accounting Study Programme Faculty of Economics and Business Universitas Negeri Surabaya, 2025)
This study examines how financial distress and profitability impact audit delay in healthcare companies before and during a pandemic. While many firms face economic challenges and delayed financial reporting during pandemics, healthcare companies demonstrate timely reporting and positive economic growth. The objective of this quantitative research is to assess these variables' influence on audit delays and determine differences in audit delay circumstances in healthcare firms before and during the pandemic. This research is a valuable reference for firms managing operations to prevent audit delays and for investors considering healthcare companies as investments, especially during unforeseen events. Utilizing statistical analysis, including partial T-tests and paired sample T-tests with SPSS version 25, the study focused on 12 healthcare companies listed on the IDX (Indonesian Stock Exchange). Findings indicate that financial distress has no effect on audit delay, while profitability negatively influences audit delay in both periods. Furthermore, differences in audit delay exist between the pre-pandemic and pandemic conditions.